2022
DOI: 10.1049/nbt2.12080
|View full text |Cite
|
Sign up to set email alerts
|

Drug delivery and anticancer activity of biosynthesised mesoporous Fe2O3nanoparticles

Abstract: Mesoporous magnetic nanoparticles of haematite were synthesised using plant extracts according to bioethics principles. The structural, physical and chemical properties of mesoporous Fe2O3 nanoparticles synthesised with the green chemistry approach were evaluated by XRD, SEM, EDAX, BET, VSM and HRTEM analysis. Then, their toxicity against normal HUVECs and MCF7 cancer cells was evaluated by MTT assay for 48 h. These biogenic mesoporous magnetic nanoparticles have over 71% of doxorubicin loading efficiency, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Oladipo and co-workers [ 166 ] fabricated hydrophilic bimetallic gold/platinum (AuPt) NPs using a Phragmites australis leaves aqueous extract and demonstrated their ability to efficiently deliver doxorubicin to breast and lung cancer cells. Recently, Zadeh and co-workers [ 167 ] reported on the ability of Mentha piperita -formulated Fe 2 O 3 NPs to deliver doxorubicin in MCF-7 cells; the nanoparticle DDS was shown to more significantly inhibit the tested cancer cells compared to that of the free anticancer drug. A limited number of drug delivery studies involving bimetallic NPs has been reported, thus there is still scope for the investigation of new combinations.…”
Section: Metal Nanoparticles In Cancer Treatmentmentioning
confidence: 99%
“…Oladipo and co-workers [ 166 ] fabricated hydrophilic bimetallic gold/platinum (AuPt) NPs using a Phragmites australis leaves aqueous extract and demonstrated their ability to efficiently deliver doxorubicin to breast and lung cancer cells. Recently, Zadeh and co-workers [ 167 ] reported on the ability of Mentha piperita -formulated Fe 2 O 3 NPs to deliver doxorubicin in MCF-7 cells; the nanoparticle DDS was shown to more significantly inhibit the tested cancer cells compared to that of the free anticancer drug. A limited number of drug delivery studies involving bimetallic NPs has been reported, thus there is still scope for the investigation of new combinations.…”
Section: Metal Nanoparticles In Cancer Treatmentmentioning
confidence: 99%
“…7 It is widely used as a catalyst, temperature/humidity sensor, gas sensor, and so forth; recent research revealed other previously unknown properties useful for some applications, such as medicine and lithium-ion batteries (anode material). [8][9][10][11] Humidity sensors using α-Fe 2 O 3 are manufactured mainly by hydrothermal synthesis. 4,5 Hydrothermal thin films of α-Fe 2 O 3 require a complex synthesis process.…”
Section: Forewordmentioning
confidence: 99%
“…α‐Fe 2 O 3 is an n ‐type semiconductor and thermodynamically stable crystalline phase 7 . It is widely used as a catalyst, temperature/humidity sensor, gas sensor, and so forth; recent research revealed other previously unknown properties useful for some applications, such as medicine and lithium‐ion batteries (anode material) 8–11 . Humidity sensors using α‐Fe 2 O 3 are manufactured mainly by hydrothermal synthesis 4,5 .…”
Section: Forewordmentioning
confidence: 99%
“…It is also of interest to form non-toxic coatings on magnetic nanoparticles based on mesoporous materials. Recently, Abolhasani Zadeh et al [ 104 ] proposed mesoporous hematite MNPs loaded with doxorubicin as a multifunctional theranostic agent exhibiting therapeutic activity against human MCF-7 breast cancer cells. These biomimetic mesoporous MNPs have over 71% doxorubicin loading efficiency resulting in a 50% reduction in cancer cells at a concentration of 0.5 µg·ml −1 .…”
Section: Synthetic Magnetic Nanoparticlesmentioning
confidence: 99%